LENGTH-WEIGHT RELATIONSHIPS OF 26 FISH SPECIES FROM ARTISANAL FISHERY IN ECUADOR - Coello, Dialhy (2021)
The length-weight relationship is usable for estimating biomass of organisms, determining the “wellbeing” of the individual and as input data in stock assessment models. The objective of this work was to establish the length-weight relationship of 26 species of fish present in artisanal fishery along the Ecuadorian continental coast. Total length and weight were recorded monthly, between 2012 and 2014, at sampling sites located in the coastal provinces of Ecuador. The length-weight relationship was estimated using the power model. A total of 24 commercials and two non-commercial species were analyzed, including demersal and benthic organisms. The value of the intercept was less than 0.03, while the coefficient of determination was greater than 0.98. The slope values showed three species with negative allometry (b < 3), nine species with positive allometry (b > 3) and 14 species with isometry (b = 3). Allometry is a specific characteristic of the species and intraspecific variations can be related to genetically determined effects, as well as, by sex, stage of maturity, spawning period. The parameters of the length-weight relationship presented should be taken with caution considering that they are given regardless of sex.